Crystal structure of the RNA demethylase ALKBH5 from zebrafish. Issue 6 (20th February 2014) - Chen, Weizhong; Zhang, Liang; Zheng, Guanqun; Fu, Ye; Ji, Quanjiang; Liu, Fange; Chen, Hao; He, Chuan
Abstract : ALKBH5, a member of AlkB family proteins, has been reported as a mammalian N 6 ‐methyladenosine (m 6 A) RNA demethylase. Here we report the crystal structure of zebrafish ALKBH5 (fALKBH5) with the resolution of 1.65 Å. Structural superimposition shows that fALKBH5 is comprised of a conserved jelly‐roll motif. However, it possesses a loop that interferes potential binding of a duplex nucleic acid substrate, suggesting an important role in substrate selection. In addition, several active site residues are different between the two known m 6 A RNA demethylases, ALKBH5 and FTO, which may result in their slightly different pathways of m 6 A demethylation. Abstract : The crystal structure of ALKBH5 from zebrafish. fALKBH5 is comprised of a conserved jelly‐roll motif. fALKBH5 possesses a loop discriminating against duplex nucleic acids. Several active site residues are different between fALKBH5 and FTO. The structure may help understand the RNA demethylation mechanism.